2021
DOI: 10.1038/s41598-020-79721-0
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal collagenase as a novel therapeutic approach in an experimental model of colorectal peritoneal carcinomatosis

Abstract: The usefulness of local collagenase in therapeutic approaches to solid tumors has been tested recently. In this study, we evaluate the safety and efficacy of intraperitoneal collagenase associated or not to mitomycin for treatment of colorectal peritoneal metastases in an experimental rat model. Using a fixed-dose procedure, we found that a dose of collagenase of 37 IU/mL administered for 15 min with a hyperthermia pump at 37.5 °C, both in isolation or associated to sequential treatment with intraperitoneal mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…We had demostrated that lavage the peritoneal cavity for 30 minutes with 50000 or 100000CDU of collagenase diluted in 1.5L of saline solution between 36-38ºC is safe and does not generate any sign of toxicity in the treated animals. This conclusion allows us, together with the e cacy data previously obtained in a rat model [5], to propose to the health authorities the use of collagenase lavage of the peritoneal cavity in a clinical trial for the conditioning or treatment of solid peritoneal tumors.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…We had demostrated that lavage the peritoneal cavity for 30 minutes with 50000 or 100000CDU of collagenase diluted in 1.5L of saline solution between 36-38ºC is safe and does not generate any sign of toxicity in the treated animals. This conclusion allows us, together with the e cacy data previously obtained in a rat model [5], to propose to the health authorities the use of collagenase lavage of the peritoneal cavity in a clinical trial for the conditioning or treatment of solid peritoneal tumors.…”
Section: Discussionmentioning
confidence: 80%
“…An important point is the activity time of collagenase, in previous studies, same articles had demonstrated that at 30 minutes collagenase activity is residual using in peritoneal cavity of mice [5,13]; in our assay and considering the high concentration of collagen existing in the peritoneal cavity, we are sure that in 30 minutes the catalytic activity of the enzyme has been "exhausted".…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Intra-tumoral or intravenous injection of collagenase increased the diffusion of large drug molecules in tumor models (54). Intraperitoneal administration of collagenase was reported to increase the e cacy of chemotherapy by cleaving the tumor stroma in a rat model of colorectal cancer peritoneal metastasis (55). Ocriplasmin is used to remove adhesions in symptomatic vitreomacular adhesion (51).…”
Section: Prognostic Signi Cance Of Col1a1 and Col5a1 For Caf In Ltration In Other Cancersmentioning
confidence: 99%
“…This type of transfection resulted in temporary action, which offers a higher safety in case of adverse effects. Due to the transient effect, repeated infusions are needed for an optimal effect [58].…”
Section: Route Of Car-t Administration Cells In Pcmentioning
confidence: 99%